Long-Term Savings as a Source of Oil Palm Replanting Financing - Vinota, Livia; Maryadi, Maryadi; Bidarti, Agustina (Jurnal Social Economic of Agriculture, 2024)
Replanting activities are one of the ways to maintain the productivity of oil palm plants. The large costs required in replanting indicate that financial planning is needed to ensure the implementation of replanting can be realized properly. This study aims to calculate the value of savings to prepare for the needs of oil palm replanting funds and provide recommendations for the implementation plan of long-term savings activities that can be carried out by oil palm farmers. This research method uses a quantitative-qualitative method. The key informants in this study were officers at KPKS Suka Makmur and employees at Bank Sumsel Babel. The informants were selected by purposive sampling by considering their expertise in oil palm replanting activities and long-term savings products. Based on the results of the research, it is known that the value of savings that must be prepared by farmers in one month is IDR 294,256.54 per hectare. Farmers can save their savings in two schemes, which are using an institutional account or a personal account. It is expected that farmers can prepare replanting funds through regular monthly savings through long-term savings in the name of an institution or group. In addition, there is a need for socialization and discussion by cooperatives or farmer groups to their members regarding the future financial plans of oil palm farming so that farmers can properly prepare for the needs of oil palm replanting funds